Three-Dimensional Pompon-like MnO2/Graphene Hydrogel Composite for Supercapacitor. (20th August 2016) - Zhang, Ningshuang; Fu, Chaopeng; Liu, Dan; Li, Yanling; Zhou, Haihui; Kuang, Yafei
Graphical abstract: A three-dimensional nanocomposite of pompon-like MnO2 /graphene hydrogel was prepared. The 3D graphene hydrogel not only provides a good support to stabilize MnO2 but also facilitate the fast ion mobility and electron transfer. The composite exhibited a good capacitive performance (445.7 F g −1 at 0.5 A g −1 ) and stability (82.4% retention after 5000 cycles). Highlights: A three-dimensional nanocomposite of pompon-like MnO2 /graphene hydrogel was prepared. GH provides a good support to stabilize MnO2 and facilitate the electron transfer. The composite exhibited a good capacitive performance (445.7 F g −1 at 0.5 A g −1 ). The composite showed excellent stability (82.4% retention after 5000 cycles). Abstract: Micro-nanostructured pompon-like MnO2 /graphene hydrogel (GH) composites with different mass ratios are prepared for supercapacitor electrodes. The morphology and structure are characterized by a range of electron microscopy and other techniques. The electrochemical performance of the prepared electrodes is investigated, and the MnO2 /graphene hydrogel composite electrode with a MnO2 content of 50% delivers a specific capacitance of 445.7 F g −1 at a current density of 0.5 A g −1, and the specific capacitance remained 82.4% of the initial value after 5000 cycles. The high performance is ascribed to the 3D pompon-like micro-nanostructure of MnO2 /graphene hydrogel that not only provides a good support to stabilize MnO2 but also facilitate the fast ion mobility and electron transfer.